Topografia do cone medular da paca (Agouti paca, Linnaeus - 1766) - scavone, Alessandra Regina Freixo [UNESP]; Guimarães, Gregório Correa [UNESP]; Rodrigues, Victor Hugo Vieira; Sasahara, Tais Harumi de Castro; Machado, Márcia Rita Fernandes [UNESP] (My University, 2007)
We object in this work to determine the skeleton sintopy of the medular cone termination of the paca relating to the lumbar and sacral vertebrae, thus aiming at establishing morphometric and topographical parameters of the medular cone in this specie. We accomplished the dissection through skin incision, subcutaneous divulsion and dissection of the vertebral column dorsal region musculature, sectioning and removing the vertebrae arcs for better visualization of the spinal medulla. After the individualization of the medular cone, we registered the anatomical aspects of interest, emphasizing the basis and its apex in relation to the vertebrae, following the measuring of the region using a caliper rule; photographs and schematic drawing were made to register the findings of studied specimens.
Topography of the medullar cone in the paca (Agouti paca, Linnaeus - 1766)
Keywords: Anatomy; Medulla; Paca; Agouti paca